2021
DOI: 10.1155/2021/4792309
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Patients with Malignancy Admitted to the Intensive Care Units: A Prospective Study

Abstract: Introduction. Decisions regarding whether advanced cancer patients should be admitted to the ICU are based on a complex suite of considerations, including short- and long-term prognosis, quality of life, and therapeutic options to treat cancer. We aimed to describe demographic, clinical, and survival data and to identify factors associated with mortality in critically ill advanced cancer patients with nonelective admissions to general ICUs. Materials and Methods. Critically ill adult (≥18 years old) cancer pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
8
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 23 publications
3
8
2
1
Order By: Relevance
“…On the contrary, the delayed strategy of CRRT was associated with increased risk, similar to the result in the ELAIN randomized clinical trial [30]. In addition, vasopressors therapy and the presence of malignancy were also risk factors for mortality, and the association has been reported in previous studies [31][32]. It's noteworthy that our study was observed marginally lower mortality with higher body temperature.…”
Section: Discussionsupporting
confidence: 89%
“…On the contrary, the delayed strategy of CRRT was associated with increased risk, similar to the result in the ELAIN randomized clinical trial [30]. In addition, vasopressors therapy and the presence of malignancy were also risk factors for mortality, and the association has been reported in previous studies [31][32]. It's noteworthy that our study was observed marginally lower mortality with higher body temperature.…”
Section: Discussionsupporting
confidence: 89%
“…A prevalence of solid tumors can be observed, which corroborates other studies (Abou Dagher et al, 2017; Assi et al, Research, Society and Development, v. 11, n. 9, e0611931452, 2022(CC BY 4.0) | ISSN 2525-3409 | DOI: http://dx.doi.org/10.33448/rsd-v11i9.31452 2021Cunha et al, 2018;Marcio Soares et al, 2016), however, the breast tumor was more frequently found, differing from those that showed a higher occurrence of lung cancer (Abou Dagher et al, 2017;Assi et al, 2021). As for hematological tumors, lymphoma (Hodgkin and non-Hodgkin) was the type of cancer that was present in most patients.…”
Section: Discussionsupporting
confidence: 88%
“…This fact is associated with a death rate of 53.8%, the main outcome found. The data show a higher death rate than previous studies that bring rates ranging from 21 to 43.4% (Assi et al, 2021;Hawari et al, 2016;Marcio Soares et al, 2016).…”
Section: Discussioncontrasting
confidence: 65%
See 1 more Smart Citation
“…By contrast, the delayed initiation of CRRT was associated with an increased risk of mortality, which is similar to the result of the ELAIN randomized clinical trial [ 31 ]. In addition, vasopressor therapy and the presence of malignancy were determined as risk factors for mortality in previous studies [ 32 , 33 ]. A marginally lower mortality was observed in the patients with higher body temperature in our study.…”
Section: Discussionmentioning
confidence: 99%